2020
DOI: 10.12688/f1000research.22991.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mobile technologies on cervical cancer screening practices in Lagos, Nigeria (mHealth-Cervix): Protocol for a randomised controlled trial

Abstract: Background: Incidence and mortality from cervical cancer have remained high due to many obstacles facing the implementation of organized screening programs in resource-constrained countries such as Nigeria. The application of mobile technologies (mHealth) to health services delivery has the potential to reduce inequalities, empower patients to control their health, and improve the cost-effectiveness of health care delivery. Aim: To assess the efficacy of mobile technology intervention on Pap test screening adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The trial Protocol was registered on the Pan African Clinical Trial Registry ( PACTR202002753354517 ). The detailed Protocol is published elsewhere 9 and some of the details are described below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The trial Protocol was registered on the Pan African Clinical Trial Registry ( PACTR202002753354517 ). The detailed Protocol is published elsewhere 9 and some of the details are described below.…”
Section: Methodsmentioning
confidence: 99%
“…The allocation sequence was kept in sealed opaque envelopes that were stored in locked file cabinets at the study sites until participants' assignments were completed. mHealth arm —We modified the study Protocol 9 by choosing MultiTexter Bulk SMS as the platform to deliver the mHealth text messages. Participants were sent messages containing health promotion information on cervical cancer screening twice monthly for 6 months after enrollment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among women receiving treatment for BC, Jongerius and colleagues (2019) found that mHealth interventions were effective in promoting weight loss, decreasing stress and improving the quality of life [30]. Another study [33] also predicted that after the COVID-19 pandemic, telemedicine would be integrated into the care of oncology patients; however, sufficient evidence to guide this integration has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been observed that mHealth will be integrated into the care of oncology patients in Nigeria during the COVID-19 pandemic [21], the evidence to guide this integration is lacking. Similarly, the need for culturally appropriate, research-tested mHealth interventions in this population has been documented [22].…”
Section: Introductionmentioning
confidence: 99%